PENDAMPINGAN WORKSHOP DESAIN KEMASAN DAN FOTOGRAFI PRODUK BAGI PELAKU WIRAUSAHA “UMKM PINTER” - Sita Yuliastuti Amijaya; Yordan Kristanto Dewangga; Wiyatiningsih; Vinsa Cantya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract Eye-catching product packaging is a great way to attract potential buyers. Packaging with good aesthetic value represents the expectations of potential buyers and reflects consumers' expectations for a product's contents. The design must convey the idea of the product maker to consumers. This product packaging design workshop is tailored to the needs of Micro, Small, and Medium Enterprises (MSMEs)